Impact of longitudinally and transversely polarized beams on probing CP-violating HZZ interactions at the ILC - Li Cheng; Moortgat-Pick Gudrid (EPJ Web of Conferences)
We study possible CP-violation effects of the Higgs to Z-boson coupling at a future e+e− collider, e.g. the International Linear Collider (ILC). We find that the azimuthal angular distribution of the muon pair, produced by e+e− → HZ → Hµ+µ−, can be sensitive to such a CP-violation effect when the initial beams are transversely polarized. Based on this angular distribution, we construct a CP sensitive asymmetry and obtain this asymmetry by Whizard simulation. By comparing the SM prediction with 2σ range of this asymmetry, we estimate the limit of the CP-odd coupling in the HZZ interaction.